Ultraviolet curing resin composition and preparation method thereof

By adding and coupling the polished fibers to the ultraviolet curing resin, the mechanical properties and wear resistance of the resin are improved, the porosity is reduced, the warping problem is solved, and the resin composition with low porosity, high toughness and high wear resistance is realized.

CN119684533APending Publication Date: 2025-03-25NINGBO EXCITON TECH

Patent Information

Application Number
CN202411972838.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing ultraviolet cured resins have shortcomings in mechanical properties, impact strength and wear resistance, and the finished product has a high porosity after curing, which makes it prone to warping problems.

Method used

By adding abrasive fibers and performing coupling treatment, the mechanical properties and wear resistance of the resin are improved, while reducing porosity and improving warping problems.

Benefits of technology

The resin composition is achieved with low porosity, high toughness and high wear resistance, and the existing resin materials have high brittleness and high porosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219818490000141
    Figure BDA0005219818490000141
  • Figure HDA0005219818500000011
    Figure HDA0005219818500000011
  • Figure HDA0005219818500000021
    Figure HDA0005219818500000021
Patent Text Reader

Abstract

According to the ultraviolet curing resin composition and the preparation method thereof, the resin composition is composed of a resin solution and grinding fibers subjected to coupling treatment, and by adding the grinding fibers, the mechanical property, the impact strength and the wear resistance of a material are improved, the porosity of a printed piece is reduced, and the warping problem of a printed model is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to an ultraviolet light-curable resin composition and a preparation method thereof. Background Art

[0002] Additive manufacturing technology is a technology that directly manufactures three-dimensional objects layer by layer through computer three-dimensional control software or three-dimensional printing equipment. According to different molding methods, it can be divided into fused deposition modeling technology, stereolithography technology, photosensitive polymer injection technology, powder laser sintering and stereolithography technology. Among them, stereolithography technology is a well-developed additive manufacturing technology. This technology uses ultraviolet-sensitive liquid resin as raw material, and uses photopolymerization reaction to scan and cure liquid resin layer by layer to achieve layer-by-layer molding. This technology has been widely used in many fields such as aerospace manufacturing, automobile manufacturing, bioengineering, and integrated device manufacturing. This technology has the characteristics of simple, fast and economical manufacturing.

[0003] Printing consumables are the key to the performance and application of devices. The photosensitive resins that currently dominate the market are mainly high-strength photosensitive resins. However, due to the high cross-linking density of the polymer after curing, the molded parts have poor flexibility and impact resistance, and are easily broken under the action of external forces, which limits their application. The flexible resins currently developed in the market have low strength, are easy to deform, have poor molding, and the molded parts are not resistant to folding, and the degree of curing is not high.

[0004] In the photocuring technology, curing shrinkage and warping have always been difficult to solve. Taking the mechanism of photocuring free radical polymerization as an example, the photocuring reaction is completed instantly, and the internal stress caused by curing shrinkage is difficult to release in time, which is very likely to cause material defects and warping, resulting in reduced performance and stability of the material, and a greater impact on the dimensional accuracy of the printed product.

[0005] CN201711136900.9 discloses a new type of fast-curing, low-shrinkage 3D printing resin, including: 40-50 parts of polyurethane acrylate prepolymer; 10-30 parts of active diluent; 1-5 parts of photoinitiator; 0.1-10 parts of auxiliary agent. The main component of the 3D printing resin is resin, which is characterized by high brittleness and poor toughness. In addition, the resin is easy to shrink, and its application value is not high in actual production.

[0006] CN201810531974.0 discloses a light-heat dual-curing 3D printing resin composition, including: 66-86 parts of free radical photosensitive resin, 9-29 parts of heat-curable epoxy resin, 1-4 parts of free radical photoinitiator, and 1-3 parts of latent thermal curing agent. This invention patent adopts the light-heat dual-curing mode molding, the steps are relatively cumbersome, the actual production cost is high, and there is no report on the mechanical properties.

[0007] CN201810480617.6 discloses an environmentally and human-friendly plant oil-based UV-curable 3D printing resin, including: palm oil-based palm oil polyester acrylate; soybean oil-based epoxidized soybean oil acrylate (AESO); glucose oxidase (GOX); free radical initiator; auxiliary agent; active diluent; polyhydroxyalkanoate (PHA); polyhydroxybutyrate (PHB). The 3D printed finished product can be biodegraded. The advantage is that it is degradable and environmentally friendly, and the disadvantage is that the tensile strength is not high, which is not suitable for some industries with high requirements.

[0008] CN201910190173.7 discloses a high-strength, high-temperature resistant 3D printing resin, including: 10-30 parts of rigid alicyclic epoxy resin, 15-25 parts of flexible alicyclic epoxy resin, 40-70 parts of prepolymer, 10-18 parts of oxetane reactive diluent, 1-3 parts of functionalized nanoparticles, 1-3 parts of color additives, 1-2 parts of solubilizers, 5-10 parts of unsaturated polyester resin, 0.5-1 parts of ammonium isocyanate, 5-8 parts of polycarbonate, 5-7 parts of cyclohexane copper powder, and 2-5 parts of diethyl phthalate. The invention mentions that it has good mechanical strength, but there is no data reported. Moreover, pure resin materials generally have large curing shrinkage and poor impact toughness.

[0009] CN201911084468.2 discloses a DLP type light-cured 3D printing resin, comprising a mercapto carboxylic acid ester compound, an allyl or triacrylate compound, a polyurethane acrylate, a photoinitiator, a diluent, a defoamer and an antioxidant. The bending strength of the 3D printed strip of the invention is 95MPa and the tensile strength is 53MPa, which is limited in practical application.

[0010] CN201911311274.1 discloses a photosensitive resin containing micro-nano wax powder, the photosensitive resin includes 0.1%-5% photoinitiator, 0.05%-2% ultraviolet absorber, 0.15-3% dispersant, 0.001%-0.5% color additive, 0.1%-2% coupling agent, 0.01%-0.05% defoamer, 5%-85% active monomer, 5%-90% micro-nano wax powder, 10%-80% active oligomer. The steps of this invention are relatively complicated, and there is no relevant report on mechanical strength.

[0011] CN202010024437.4 discloses a UV-curable elastic resin for 3D printing, including 5-15 parts of carboxyl-terminated butadiene-modified polyurethane acrylate, 25-60 parts of active monomers, 0.01-0.2 parts of inhibitors, 1-10 parts of photoinitiators, 0.02-1 parts of defoamers, 0.02-1 parts of leveling agents, 0.03-2 parts of pigments, and 2-5 parts of fillers. The prepared material has a tensile strength of 25.65MPa and an elongation at break of 190%. The advantage is that it has a certain elasticity, but the disadvantage is that the steps are relatively complicated and the production cycle is long.

[0012] CN202010346027.1 discloses a soft light-curable 3D printing resin material, including 30-50 parts of oligomers, 40-60 parts of monomers, 0.1-6 parts of photoinitiators and 0-4 parts of additives, wherein the additives include UV color paste, leveling agent, defoamer, dispersant, ultraviolet absorber, sensitizer, inhibitor and inorganic filler. The products printed by the 3D printing resin material of the invention have good folding resistance, but the disadvantage is that the tensile strength is relatively low.

[0013] CN202111201955.X discloses a hollow porous silica microsphere enhanced light-cured 3D printing composite material, including 40-55 parts of acrylate resin prepolymer, 45-55 parts of active diluent monomer, 1-2 parts of photoinitiator, 0.05-0.1 parts of ultraviolet absorber and 0.1-10 parts of hollow porous silica, wherein the acrylate resin prepolymer is a mixture of 55-65 parts of aliphatic polyurethane acrylate and 35-45 parts of aromatic polyurethane acrylate by mass fraction. The cured material has good mechanical properties, but the curing shrinkage is high.

[0014] CN202011398158.0 discloses a photocurable chopped quartz fiber reinforced silica ceramic paste, wherein bundled chopped quartz fibers are first made into single-filament chopped quartz fibers, and then SiO2 powder is mixed with a powder dispersant and ball-milled in a ball mill. A photoinitiator and a silane coupling agent are then added to the resin mixture, and a photocurable resin system is obtained by ball milling. The photocurable resin system is added to the solid mixture, and a light absorber is dripped into the mixture. The mixture is stirred and placed in a homogenizer for mixing and evacuation to obtain a silica ceramic paste. Finally, the single-filament chopped quartz fibers are added to the silica ceramic paste and mixed to obtain a ceramic paste. There is no report on the mechanical strength of the resin paste.

[0015] CN202011397781.4 discloses a pre-treated dual-curing 3D printing resin, including 19%-78% oligomer, 1%-9% free radical initiator, 0.5%-5% cationic initiator, 0.5%-5% hybrid curing photoinitiator, 0.2%-4% auxiliary agent, 10%-35% active diluent, 13%-62% cationic monomer, and 5%-20% hybrid monomer. The printing resin has low shrinkage, good curing performance, and excellent mechanical properties. However, pure resin materials generally have poor toughness.

[0016] CN202111587812.7 discloses a new type of light-cured 3D printing resin material, the molecular chain structure of the resin material is dendritic, the main chain is polyacrylate, the side chain includes acrylate group, modified silicone oxygen flexible long chain, and introduces fluorine-containing active monomers and fluorine-containing organic toughening agents into the cross-linked network, which is composed of 30-50 parts of acrylate, 5-20 parts of silicone active chain, 30-50 parts of active diluent, 0.5-4 parts of free radical photoinitiator, and 0.05-4 parts of auxiliary agent. The material has good printing toughness, low curing shrinkage and warpage.

[0017] CN202110554184.6 discloses a water-based UV-curable resin having two ammonium salt hydrophilic groups. Water can be added to directly dilute the resin, which is cured by ultraviolet light irradiation. The resin has the characteristics of fast curing speed, but no reports have been made on its mechanical properties.

[0018] CN202211619791.7 discloses a UV light-curing 3D printing resin, wherein anhydride compounds, polymerization inhibitors, hydroxy acrylates and catalysts are sequentially added to a reaction kettle and stirred at 50-120°C for 1-12 hours; then bisphenol A epoxy resin, catalyst, polymerization inhibitors are added, and finally acrylate monomers are added. The product has fast curing speed, good toughness and low shrinkage.

[0019] JP Patent Publication No. 9-151223 discloses a photocurable resin composition, including urethane (meth) acrylate, N-vinylamide monomer, photoinitiator, etc. The maximum tensile strength of the prepared material is only 0.8 kgf / mm 2 .

[0020] CN202310651518.0 discloses an organic-inorganic composite 3D printing resin, which includes the following raw materials in parts by weight: 10-30 parts of organosilicon-modified polyurethane acrylic resin, 55-85 parts of small molecule active diluent, 5-30 parts of shell powder, and 4-6 parts of free radical photoinitiator. The printing resin has the characteristics of low shrinkage, high precision, and high strength.

[0021] CN202310452296.X discloses a superhard dental model light-cured 3D printing resin material, including 40-60 parts of active diluent monomer, 40-60 parts of polyurethane acrylate oligomer, 1-3 parts of photoinitiator, and 3-5 parts of hydrophobically modified titanium dioxide nanomaterial. The resin material has low viscosity, fast curing speed, and certain strength and toughness.

[0022] Based on the above analysis, a UV-curable resin composition is provided for application in the field of three-dimensional additive manufacturing, in order to have excellent mechanical strength, high toughness, high wear resistance, low porosity and low warping, which has significant application value. Summary of the invention

[0023] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a UV-curable resin composition and a preparation method thereof, to improve the mechanical properties, impact strength and wear resistance of the material by adding ground fibers, to reduce the porosity of the printed part, and to improve the warping problem of the printed model. In order to overcome the shortcomings of the above-mentioned prior art, the present invention aims to provide a UV-curable resin composition and a preparation method thereof, which have the characteristics of low porosity, high toughness, high wear resistance, etc.

[0024] In order to solve the above technical problems, the present invention adopts the following technical solutions.

[0025] The present invention first provides a UV-curable resin composition, comprising component A and component B.

[0026] Component A is a resin solution, comprising 40-50 parts by weight of an acrylate resin oligomer, 50-70 parts by weight of an active diluent monomer, 5-10 parts by weight of a structural stabilizer, 0.5-5 parts by weight of a photoinitiator, 0.5-5 parts by weight of an ultraviolet absorber, and 0.5-5 parts by weight of a defoamer;

[0027] Component B is a coupling-treated ground fiber;

[0028] Based on 100 parts by weight of component A and component B in total, the weight ratio of component A to component B is (80-55):(20-45).

[0029] Furthermore, based on 100 parts by weight of component A and component B in total, the weight ratio of component A to component B is (70-60):(30-40), or 65:35.

[0030] Furthermore, the acrylate resin oligomer is selected from at least one of epoxy acrylate, polyurethane acrylate, polyester acrylate and polyether acrylate.

[0031] Furthermore, the functionality of the polyurethane acrylic resin is 8-13, or 9, or 10, or 11, or 12.

[0032] Furthermore, the weight proportions of the acrylic resin oligomer are 42 parts, 45 parts, and 48 parts.

[0033] Furthermore, the active diluent monomer is at least one of hydroxyethyl methacrylate, isobornyl acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate.

[0034] Furthermore, the functionality of the reactive diluent monomer is ≤3, or is 2 or 1.

[0035] Furthermore, the weight proportion of the reactive diluent monomer is 55 parts, 60 parts, or 65 parts.

[0036] Furthermore, the structural stabilizer is at least one of polyvinyl alcohol, cellulose ether, chitosan, calcium stearate, and sodium carboxymethyl cellulose.

[0037] Furthermore, the weight proportion of the structural stabilizer is 6 parts, 8 parts, or 9 parts.

[0038] Furthermore, the photoinitiator is at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1-hydroxycyclohexyl phenyl ketone (Irgacure-184).

[0039] Furthermore, the weight proportion of the photoinitiator is 1 part, 1.5 parts, 2 parts, 3 parts, or 4 parts.

[0040] Furthermore, the ultraviolet absorber is one or more of benzotriazole, substituted acrylonitrile, triazine, salicylate, and benzophenone ultraviolet absorbers.

[0041] Furthermore, the benzophenone ultraviolet absorber is at least one of 2,4-dihydroxybenzophenone (BP-1) and 2-hydroxy-4-methoxybenzophenone (BP-3).

[0042] Furthermore, the weight proportion of the ultraviolet absorber is 1 part, 1.5 parts, 2 parts, 3 parts, or 4 parts.

[0043] Furthermore, the defoaming agent is one or more of an alcohol defoaming agent, a silicone resin defoaming agent, and a polyether-modified silicone oil defoaming agent.

[0044] Furthermore, the defoaming agent is at least one of BYK055, BYK088, BYK020, and BYK067A.

[0045] Furthermore, the weight proportions of the defoaming agent are 1 part, 1.5 parts, 2 parts, 3 parts, and 4 parts.

[0046] Furthermore, the ground fiber is an inorganic fiber, including at least one of ground glass fiber, ground asbestos fiber, ground carbon fiber, ground alumina fiber, ground zirconium oxide fiber, ground silicon carbide fiber, ground aluminum silicate fiber, ground silicon nitride fiber, ground graphene fiber, and ground basalt fiber.

[0047] Furthermore, the diameter of the ground fiber is 5-9 μm, or 6 μm, 7 μm, or 8 μm; the length is 50-200 μm, or 80 μm, 100 μm, or 150 μm.

[0048] Furthermore, the ground fiber is subjected to degreasing treatment and coupling agent treatment.

[0049] Furthermore, the ground fiber is degreased by placing the ground fiber in a high-temperature furnace protected by inert gas and degreasing it at a high temperature of 400-1400° C. (or 600° C., 800° C., 1000° C., 1200° C.) for 0.5-6 h (or 1 h, 2 h, 4 h).

[0050] Furthermore, the inert gas is high-purity nitrogen or high-purity argon with a purity of ≥99.99%.

[0051] Furthermore, the coupling agent treatment of the ground fiber comprises mixing the ground fiber, solvent and coupling agent, refluxing and drying to obtain the surface-modified ground fiber.

[0052] Furthermore, the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0053] Preferably, at least one of the silane coupling agents KH550, KH560, KH570, KH580, KH590, KH151, KH171, and KH172 is used.

[0054] Furthermore, the mass ratio of the ground fiber, the solvent and the coupling agent is (80-110): (80-110): (0.2-3).

[0055] Furthermore, the reflux temperature is 70-100°C, or 80°C, 90°C; the reflux time is 4-6h, or 5h.

[0056] The present invention also provides a method for preparing a photocurable resin composition, comprising the following steps:

[0057] Step (1), grinding fiber modification treatment

[0058] refluxing the ground fiber, the solvent, and the coupling agent to obtain a coupled ground fiber;

[0059] Step (2), preparing a resin solution

[0060] Mixing acrylate resin oligomer, active diluent monomer, structure stabilizer, photoinitiator, ultraviolet absorber and defoamer, stirring evenly to obtain a resin solution;

[0061] Step (3), preparing a resin composition

[0062] The modified ground fiber obtained in step (1) and the resin solution obtained in step (2) are mixed and rotated in an internal mixer to obtain a resin composition.

[0063] Further, in step (1), the ground fiber is subjected to a degreasing treatment and then a coupling treatment;

[0064] Furthermore, in step (1), the ground fiber is degreased by placing the ground fiber in a high-temperature furnace protected by inert gas and degreasing it at a high temperature of 400-1400°C (or 600°C, 800°C, 1000°C, 1200°C) for 0.5-6h (or 1h, 2h, 4h).

[0065] Furthermore, in step (1), the grinding fiber is further treated with a coupling agent, the grinding fiber, the solvent and the coupling agent are mixed, refluxed, and dried to obtain a surface-modified grinding fiber.

[0066] Furthermore, in step (1), the coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0067] Preferably, at least one of the silane coupling agents KH550, KH560, KH570, KH580, KH590, KH151, KH171, and KH172 is used.

[0068] Furthermore, in step (1), the mass ratio of the ground fiber, the solvent and the coupling agent is (80-110): (80-110): (0.2-3).

[0069] Furthermore, in step (1), the reflux temperature is 70-100°C, or 80°C, 90°C; and the reflux time is 4-6h, or 5h.

[0070] Furthermore, in step (2), the acrylate resin oligomer is selected from at least one of epoxy acrylate, polyurethane acrylate, polyester acrylate, and polyether acrylate.

[0071] Furthermore, in step (2), the functionality of the polyurethane acrylic resin is 8-13, or 9 or 10 or 11 or 12.

[0072] Furthermore, in step (2), the active diluent monomer is at least one of hydroxyethyl methacrylate, isobornyl acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate.

[0073] Furthermore, in step (2), the functionality of the reactive diluent monomer is ≤3, or is 2 or 1.

[0074] Furthermore, in step (2), the structural stabilizer is at least one of polyvinyl alcohol, cellulose ether, chitosan, calcium stearate, and sodium carboxymethyl cellulose.

[0075] Furthermore, in step (2), the photoinitiator is at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1-hydroxycyclohexyl phenyl ketone (Irgacure-184).

[0076] Furthermore, in step (2), the ultraviolet absorber is one or more of benzotriazole, substituted acrylonitrile, triazine, salicylate, and benzophenone ultraviolet absorbers.

[0077] Furthermore, in step (2), the benzophenone ultraviolet absorber is at least one of 2,4-dihydroxybenzophenone (BP-1) and 2-hydroxy-4-methoxybenzophenone (BP-3).

[0078] Furthermore, in step (2), the defoaming agent is one or more of an alcohol defoaming agent, a silicone resin defoaming agent, and a polyether-modified silicone oil defoaming agent.

[0079] Furthermore, in step (2), the defoaming agent is at least one of BYK055, BYK088, BYK020, and BYK067A.

[0080] Furthermore, in step (3), based on 100 parts by weight of the resin solution (A) and the ground fiber (B), the weight ratio of the resin solution to the ground fiber is (80-55):(20-45).

[0081] Furthermore, in step (3), based on 100 parts by weight of A and B in total, the weight ratio of A to B is (70-60):(30-40), or 65:35.

[0082] Furthermore, in step (3), the rotation speed of the internal mixer is set to 2000-3000 r / min, and the rotation time is 4-6 h.

[0083] Furthermore, the viscosity of the resin composition is 100-600 mPa·s.

[0084] Furthermore, the present invention provides a method for preparing a UV-curable resin composition, comprising the following steps:

[0085] Step (1): placing the ground fiber in a high-temperature furnace protected by high-purity nitrogen, degreasing at 400-1400° C. for 0.5-6 h, and kneading the ground fiber to obtain a single-filament ground fiber after cooling to room temperature, and setting aside; ultrasonically dispersing the single-filament ground fiber, anhydrous ethanol and silane coupling agent in a mass ratio of 100:100:(0.5-2), pouring the dispersed suspension into a three-necked flask, condensing and refluxing in a water bath at 80° C. for 4-6 h, and drying in a nitrogen atmosphere to obtain a surface-modified ground fiber, and setting aside; taking a small amount of the ground fiber before and after modification for contact angle testing;

[0086] Step (2): add 50 parts by weight of active diluent monomer to 40 parts by weight of resin and stir to mix, and at the same time add 5 parts by weight of structural stabilizer, 1 part by weight of photoinitiator, 1.5 parts by weight of ultraviolet absorber and 1 part by weight of defoamer to mix to obtain a resin solution; set the stirring speed to 1000-2000 r / min and the stirring time to 1-3h.

[0087] Step (3): placing the surface-modified ground fiber prepared in step (1) and the resin solution prepared in step (2) in an internal mixer at a weight ratio of (20-45):(80-55), setting the parameters to a cycle of first forward rotation for 0.5 h and then reverse rotation for 0.5 h, setting the rotation speed to 2000-3000 r / min, and the rotation time to 4-6 h, thereby obtaining a ground fiber reinforced resin composition for photocuring, wherein the viscosity of the resin composition is 100-600 mPa·s.

[0088] Furthermore, both step (2) and step (3) need to be prepared in a dark room away from light.

[0089] The present invention also provides an application of an ultraviolet light curing resin composition in three-dimensional printing.

[0090] The present invention also provides an application of a grinding fiber in three-dimensional printing, wherein the grinding fiber is a coupling-treated grinding fiber.

[0091] Compared with the prior art, the product provided by the present invention has the following advantages or functions:

[0092] The ground fiber has good wear resistance and toughness. The surface of the ground fiber is modified by coupling agent treatment, so that the ground fiber has good dispersibility in the resin system. By controlling the amount of added ground fiber, the wear resistance and toughness of the resin composition can be improved. By adding a structural stabilizer, the long-term stability of the resin composition can be guaranteed. At the same time, with reasonable process conditions, a UV-curable resin composition is prepared. The UV-curable resin composition has the characteristics of low porosity and high toughness, which solves the shortcomings of existing three-dimensional printing materials, such as high brittleness and high porosity. The raw materials of the present invention are easy to obtain and the cost is low. The process route is feasible. The prepared sample has high density and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0093] Figure 1 Schematic diagram of the reaction process of cross-linking the ground fiber and the polymer resin into an organic-inorganic hybrid three-dimensional network structure through a coupling agent;

[0094] Figure 2 This is a scanning electron microscope image of the resin composition after curing. DETAILED DESCRIPTION

[0095] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the preferred embodiments of the present invention are described in detail with reference to the drawings as follows:

[0096] Figure 1 Schematic diagram of the reaction process of cross-linking the ground fiber and the polymer resin into an organic-inorganic hybrid three-dimensional network structure through a coupling agent;

[0097] Figure 2 This is a scanning electron microscope image of the resin composition after curing.

[0098] The method for preparing a low shrinkage, high toughness and high wear-resistant resin composition provided by the present invention comprises the following steps:

[0099] Step (1), placing the ground fiber in a high-temperature furnace protected by high-purity nitrogen or high-purity argon with a purity of ≥99.99%, degreasing it at a high temperature of 400-1400°C for 0.5-6h, and kneading it after cooling it to room temperature to obtain a single-filament ground fiber for standby use; ultrasonically dispersing the single-filament ground fiber, anhydrous ethanol and a silane coupling agent in a mass ratio of 100:100:(0.5-2), pouring the dispersed suspension into a three-necked flask, condensing and refluxing it in a water bath at 80°C for 4-6h, and drying it in a nitrogen atmosphere to obtain a surface-modified ground fiber for standby use, and taking a small amount of the ground fiber before and after modification for contact angle testing;

[0100] Step (2): Add 50 parts by weight of active diluent monomer to 40 parts by weight of resin and stir to mix, and add 5 parts by weight of structural stabilizer, 1 part by weight of photoinitiator, 1.5 parts by weight of ultraviolet absorber, and 1 part by weight of defoamer to obtain a resin solution. Set the stirring speed to 1000-2000 r / min and the stirring time to 1-3 hours.

[0101] Step (3): The surface modified ground fiber prepared in step (1) and the resin solution prepared in step (2) are placed in an internal mixer at a weight ratio of (20-45): (80-55). Furthermore, the surface modified ground fiber and the resin solution are placed in an internal mixer at a weight ratio of (30-40): (70-60). The parameters are set to a cycle of first forward rotation for 0.5 h and then reverse rotation for 0.5 h. The speed is set to 2000-3000 r / min and the rotation time is 4-6 h. Thus, a ground fiber reinforced resin composition for photocuring is obtained.

[0102] The viscosity of the resin composition is 100-600 mPa·s, and further the viscosity of the resin composition is 300-500 mPa·s.

[0103] The resin composition of the present invention and the comparative resin composition were cured by irradiating a laser beam with a wavelength of 285-415 nm for 3-5 minutes to prepare test specimens.

[0104] The material testing device or testing method provided by the present invention is described as follows:

[0105] 1. Contact angle: tested using CA-100B contact angle meter from Yingnuo Company.

[0106] 2. Viscosity: tested using Brookfield DVS+ rotational viscometer.

[0107] 3. Porosity: The porosity shall refer to GB / T 25995-2010 standard.

[0108] 4. Tensile properties: The tensile properties are carried out in accordance with GB / T 23805 standard. The test is carried out on a mechanical properties testing machine with a loading rate of 0.5 mm / min. The sample size (width × thickness) is 10 mm × 4 mm, and there are 10 samples. The average value is calculated.

[0109] 5. Bending performance: Bending performance is carried out in accordance with GB / T 9341-2008 standard. The test is carried out on a mechanical properties testing machine with a loading rate of 0.5mm / min. The sample size (length × width × thickness) is 36mm × 4mm × 3mm, the span is 30mm, the number is 10, and the average value is calculated.

[0110] 6. Fracture toughness: Fracture toughness is tested by single edge notched beam method (SENB), which is carried out on a mechanical properties testing machine with a loading rate of 0.5 mm / min. The sample size (length × width × thickness) is 50 mm × 3.5 mm × 7 mm, the middle notch depth is 3.5 mm (thickness direction), the span is 30 mm, and there are 10 samples. The average value is calculated.

[0111] Example 1

[0112] A UV-curable resin composition and a preparation method thereof, the preparation method comprising:

[0113] Step (1) Grinding fiber modification treatment

[0114] The ground carbon fiber is placed in a high-temperature furnace protected by high-purity argon with a purity of 99.99%, and degreased at 1200°C for 30 minutes. After cooling to room temperature, the single-filament ground carbon fiber is kneaded to obtain a standby; 100 parts by weight of the single-filament ground carbon fiber, 100 parts by weight of anhydrous ethanol and 0.5 parts by weight of silane coupling agent KH171 are mixed and ultrasonically dispersed, and the dispersed suspension is poured into a three-necked flask, condensed and refluxed in a water bath at 80°C for 4 hours, and dried in a nitrogen atmosphere to obtain a surface-modified ground carbon fiber, which is placed in a drying oven for standby use, and a small amount of the ground carbon fiber before and after modification is taken for contact angle testing;

[0115] Step (2) Preparation of resin solution

[0116] Under light-proof conditions, 50 parts by weight of trimethylolpropane triacrylate monomer was added to 40 parts by weight of 8-functionality polyurethane acrylate resin and stirred and mixed. At the same time, 5 parts by weight of structural stabilizer carboxymethyl cellulose sodium salt, 1 part by weight of photoinitiator TPO, 1.5 parts by weight of ultraviolet absorber BP-1, and 1 part by weight of defoamer BYK055 were added and mixed to obtain a resin solution. The stirring speed was set to 1500 r / min and the stirring time was 1 hour until the solution was mixed evenly.

[0117] Step (3) Preparation of resin composition

[0118] Under light-proof conditions, the surface-modified ground carbon fiber prepared in step (2) and the resin solution prepared in step (3) are placed in an internal mixer at a weight ratio of 35:65, and the parameters are set to a cycle of first forward rotation for 0.5 h and then reverse rotation for 0.5 h, the speed is set to 2500 r / min, and the rotation time is 4 h, so as to obtain a ground fiber reinforced resin composition for photocuring.

[0119] Example 2

[0120] The difference from Example 1 is that in the first step of grinding carbon fiber modification treatment in Example 2, the addition ratio of silane coupling agent KH171 is 1 part by weight.

[0121] Example 3

[0122] The difference from Example 1 is that in the third step of preparing the resin composition in Example 3, the weight ratio of the surface-modified ground carbon fiber to the resin solution is 30:70.

[0123] Example 4

[0124] The difference from Example 1 is that in the third step of preparing the resin composition in Example 4, the weight ratio of the surface-modified ground carbon fiber to the resin solution is 40:60.

[0125] Example 5

[0126] The difference from Example 1 is that in the first step of grinding carbon fiber modification treatment in Example 5, the silane coupling agent is KH550.

[0127] Example 6

[0128] The difference from Example 1 is that in Example 6, the first step of grinding the fiber is grinding glass fiber, and the treatment temperature is 600° C. for 0.5 h.

[0129] Comparative Example 1

[0130] The difference from Example 1 is that in the first step of grinding the fibers in Comparative Example 1, no silane coupling agent KH171 is added.

[0131] Comparative Example 2

[0132] The difference from Example 1 is that in the third step of preparing the resin composition in Comparative Example 2, no surface-modified ground fiber is added.

[0133] Comparative Example 3

[0134] The difference from Example 1 is that in the third step of preparing the resin composition of Comparative Example 3, the weight ratio of the surface-modified ground carbon fiber to the resin solution is 65:35.

[0135] The contact angle data of the modified fiber of the present invention before and after modification, the viscosity of the resin composition and the comparative resin composition, and the curing condition of irradiating a laser beam at a wavelength of 415 nm for 5 minutes were used to prepare test specimens. The mechanical property test results after curing are shown in Table 1.

[0136] Table 1 Water drop angle of modified ground fiber, viscosity of resin composition, porosity of test piece after curing and mechanical properties data

[0137]

[0138] It can be seen from the test results of the above embodiments and comparative examples that the contact angle of the ground fiber becomes larger and the hydrophobicity is enhanced after modification. Compared with comparative examples 1 to 3, embodiments 1 to 5 have better mechanical properties and lower porosity. Appropriate addition of silane coupling agent to modify the surface of the ground fiber can be well dispersed in the resin system, and has a good bonding effect with the resin, which helps to improve the mechanical properties. The ratio of ground fiber to resin has good mechanical properties within a certain range. If the ratio of ground fiber is too low, the material is brittle and the mechanical properties will deteriorate. If the ratio of ground fiber is too high, some of the ground fibers are less wrapped by the resin matrix, and the load cannot be effectively transferred to the fiber, resulting in a decrease in mechanical properties. The mechanical strength of embodiment 6 is lower than that of embodiment 1, indicating that the mechanical properties of the material are different when different ground fibers are added, but the mechanical properties will be improved compared to no ground fibers. Inorganic fiber materials have the characteristics of strong wear resistance and good flexibility. By adding inorganic fibers to the resin, the wear resistance and flexibility of the material will be greatly improved. The embodiment provided by the present invention relates to a UV-curable resin composition and a preparation method thereof. By controlling the type and proportion of additives and adopting reasonable process conditions, a low-porosity, high-toughness, and high-wear-resistant resin material is prepared. The grinding fiber is modified by a coupling agent to help improve the dispersibility and compatibility of the fiber in the resin system, and the prepared resin composition can maintain uniformity and stability for a long time. The material cost of the present invention is low, the preparation process is simple, and it is suitable for mass production, which solves the problems of large shrinkage, low strength, poor toughness and wear resistance of existing three-dimensional printing materials.

[0139] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.

Claims

1. A UV-curable resin composition comprising component A and component B, Component A is a resin solution, comprising 40-50 parts by weight of an acrylate resin oligomer, 50-70 parts by weight of an active diluent monomer, 5-10 parts by weight of a structural stabilizer, 0.5-5 parts by weight of a photoinitiator, 0.5-5 parts by weight of an ultraviolet absorber, and 0.5-5 parts by weight of a defoamer; Component B is a coupling-treated ground fiber; Based on 100 parts by weight of component A and component B in total, the weight ratio of component A to component B is (80-55):(20-45).

2. The resin combination according to claim 1, characterized in that: The acrylate resin oligomer is selected from at least one of epoxy acrylate, polyurethane acrylate, polyester acrylate and polyether acrylate.

3. The resin combination according to claim 2, characterized in that: The functionality of the polyurethane acrylic resin is 8-13.

4. The resin combination according to claim 1, characterized in that: The active diluent monomer is at least one of hydroxyethyl methacrylate, isobornyl acrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate.

5. The resin combination according to claim 1, characterized in that: The structural stabilizer is at least one of polyvinyl alcohol, cellulose ether, chitosan, calcium stearate, and sodium carboxymethyl cellulose.

6. The resin combination according to claim 1, characterized in that: The photoinitiator is at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) and 1-hydroxycyclohexyl phenyl ketone (Irgacure-184).

7. The resin combination according to claim 1, characterized in that: The ultraviolet absorber is one or more of benzotriazole, substituted acrylonitrile, triazine, salicylate and benzophenone ultraviolet absorbers.

8. The resin combination according to claim 1, characterized in that: The defoaming agent is one or more of an alcohol defoaming agent, an organic silicone resin defoaming agent, and a polyether-modified silicone oil defoaming agent.

9. The resin combination according to claim 1, characterized in that: The ground fiber is an inorganic fiber, including at least one of ground glass fiber, ground asbestos fiber, ground carbon fiber, ground alumina fiber, ground zirconium oxide fiber, ground silicon carbide fiber, ground aluminum silicate fiber, ground silicon nitride fiber, ground graphene fiber and ground basalt fiber.

10. The resin combination according to claim 1, characterized in that: The ground fiber is subjected to degreasing treatment and coupling agent treatment.

11. The resin combination according to claim 10, characterized in that: The degreasing treatment of the ground fiber is to place the ground fiber in a high-temperature furnace protected by inert gas and perform degreasing treatment at a high temperature of 400-1400° C. for 0.5-6 hours.

12. The resin combination according to claim 10, characterized in that: The coupling agent treatment of the ground fiber comprises mixing the ground fiber, solvent and coupling agent, refluxing and drying to obtain the surface-modified ground fiber.

13. The resin combination according to claim 12, characterized in that: The coupling agent is at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

14. The resin combination according to claim 12 or 13, characterized in that: The mass ratio of the ground fiber, the solvent and the coupling agent is (80-110): (80-110): (0.2-3).

15. The resin combination according to claim 12 or 13, characterized in that: The reflux temperature is 70-100° C.; the reflux time is 4-6 hours.

16. A method for preparing the resin composition according to any one of claims 1 to 15, comprising the following steps: Step (1), grinding fiber modification treatment refluxing the ground fiber, the solvent, and the coupling agent to obtain a coupled ground fiber; Step (2), preparing a resin solution Mixing acrylate resin oligomer, active diluent monomer, structure stabilizer, photoinitiator, ultraviolet absorber and defoamer, stirring evenly to obtain a resin solution; Step (3), preparing a resin composition The ground fiber obtained in step (1) and the resin solution obtained in step (2) are mixed and rotated in an internal mixer to obtain a resin composition.

17. The method for preparing the resin composition according to claim 16, characterized in that: The rotation speed of the internal mixer is set to 2000-3000 r / min, and the rotation time is 4-6 h.

18. The method for preparing the resin composition according to claim 16, characterized in that: The viscosity of the resin composition is 100-600 mPa·s.

19. Use of the UV-curable resin composition according to any one of claims 1 to 15 in three-dimensional printing.

20. Use of a ground fiber in three-dimensional printing, wherein the ground fiber is the ground fiber in the ultraviolet light-curable resin composition according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Novel quickly-cured 3D printing resin with low shrinkage rate

    CN107880223A

  • Vegetable-oil-based ultraviolet-photocured 3D printing resin friendly to environment and human bodies

    CN108587100A

  • Photo-thermal double-curing 3D printing resin composition

    CN108948280A

  • High-strength high-temperature-resistant resin for 3D printing

    CN109957212A

  • DLP type light-curable 3D printing resin and preparation method thereof

    CN111004355A

Cited By

  • UV curing composition, photovoltaic cell containing UV curing composition and application of UV curing composition

    CN120865827A

  • A uv-curable composition, photovoltaic cell containing same and use thereof

    CN120865827B